Increased FDG-PET/CT pericardial uptake identifies acute pericarditis patients at high risk for relapse. (15th November 2018) - Gerardin, Christel; Mageau, Arthur; Benali, Khadija; Jouan, Fanny; Ducrocq, Gregory; Alexandra, Jean-Francois; van Gysel, Damien; Papo, Thomas; Sacre, Karim
Abstract: Objectives: We aimed to evaluate the prognostic value of FDG pericardial uptake using FDG-PET/CT in patients admitted for acute pericarditis with pericardial effusion. Methods: In this monocentric retrospective cohort study, all patients admitted for idiopathic acute pericarditis with pericardial effusion from January 2009 to December 2016 who underwent a FDG-PET/CT at diagnosis were considered. Pericardial FDG uptake was measured by generating a volume of interest to calculate the maximal standardized uptake value. The primary outcome was the pericarditis relapse rate during follow-up. Results: FDG-PET/CT was performed 23 [7–99] days after diagnosis in 39 patients (52 [18–83] years, 43.6% of women) admitted for acute pericarditis with pericardial effusion. During a median follow-up period of 7.6 [2.4–77.2] months, 7 (17.9%) patients suffered pericarditis relapse that occurred 3.8 [1.6–14.6] months after FDG-PET CT. In the multivariable analysis, pericardial FDG uptake at diagnosis (OR: 16.6; 95% confidence interval [CI]: 1.25 to 220.8; p  = 0.033) was independently associated with pericarditis relapse. Eventually, patients with pericardial FDG uptake at diagnosis had a higher recurrence rate during follow up ( p  = 0.047). Conclusions: In acute pericarditis with pericardial effusion, increased FDG-PET/CT pericardial uptake is associated with a higher risk for relapse. Highlights: Pericarditis relapse is a major complication of acute pericarditis Relapsing pericarditis is ascribed to an auto-inflammatory process FDG-PET CT is the mainstay diagnostic test for nuclear imaging of cardiac inflammation FDG-PET CT pericardial uptake identifies patients at risk for pericarditis relapse